La mise en politique de la transition énergétique : la durabilité à l’épreuve des conflits de temporalités - Laura Durand; Annaig Oiry; Angélique Palle (Temporalités)
Energy transition is today one of the key figures in the more general concept of sustainable development. It is marked by the double temporality of urgency and the long term. Implementing the transition generates conflicts, especially regarding large infrastructure projects. This article analyzes them by crossing the temporalities and scales of action of the various stakeholders. It highlights the tensions that exist between climate emergency and sustainability in the implementation of the energy transition, but also the complexity of the temporalities claimed by the actors, which sometimes intertwine, but other times are opposed, thus generating conflict. The article is divided into three parts, organized around the European, national and local levels of the energy transition. Three sets of fieldwork support our analyses: a survey of the European Network of Electricity System Operators (ENTSO-E) in charge of the investment plan for electricity transmission networks, the study of conflicts related to the establishment of marine renewable energies in France, and a Greek case study on conflicts related to wind farm projects in Crete.